2018
DOI: 10.3389/fpls.2018.00307
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Iron Concentration as Affected by Nitrogen Fertilization and Their Localization in Wheat Grain

Abstract: Nearly half of the world cereal production comes from soils low or marginal in plant available zinc, leading to unsustainable and poor quality grain production. Therefore, the effects of nitrogen (N) rate and application time on zinc (Zn) and iron (Fe) concentration in wheat grain were investigated. Wheat (Triticum aestivum var. Krabat) was grown in a growth chamber with 8 and 16 h of day and night periods, respectively. The N rates were 29, 43, and 57 mg N kg-1 soil, equivalent to 80, 120, and 160 kg N ha-1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 37 publications
1
40
1
Order By: Relevance
“…As reported by Graham [4], every second, one person dies of disease related to diet. Moreover, Fe deficiency affects more than two billion individuals, or one in three people globally [7,8], while about 30% of people in developing countries and 10% of Americans and Canadians are Zn deficient [9]. The World Health Organization estimates that approximately 25% of the world's population suffers from anemia [10], and that Fe deficiency anemia led to the loss of over 46,000 disability-adjusted life years (DALYs) in 2010 alone [11].…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Graham [4], every second, one person dies of disease related to diet. Moreover, Fe deficiency affects more than two billion individuals, or one in three people globally [7,8], while about 30% of people in developing countries and 10% of Americans and Canadians are Zn deficient [9]. The World Health Organization estimates that approximately 25% of the world's population suffers from anemia [10], and that Fe deficiency anemia led to the loss of over 46,000 disability-adjusted life years (DALYs) in 2010 alone [11].…”
Section: Introductionmentioning
confidence: 99%
“…Erenoglu [9] demonstrated that biofortification of food cultivation must take into account the key role of nitrogen in Zn uptake and accumulation. The role of nitrogen in facilitating the uptake, transportation, translocation and deposit of microelements, in particular of Zn in cereal grain, has been thoroughly studied [25].The yield and quality if wheat grain depend on the characteristics of the cultivar, applied agrotechnics and environmental factors [1,26]. The cultivar also dictates wheat's technological value.…”
mentioning
confidence: 99%
“…Erenoglu [9] demonstrated that biofortification of food cultivation must take into account the key role of nitrogen in Zn uptake and accumulation. The role of nitrogen in facilitating the uptake, transportation, translocation and deposit of microelements, in particular of Zn in cereal grain, has been thoroughly studied [25].…”
mentioning
confidence: 99%
“…It was observed that status of plant mineral nutrient plays an important role in improving resistance against water stress condition. Inoculation of wheat seed with PGPB has positive role on leaf nitrogen, phosphorus, potassium, chlorophyll and relative water contents [7,22]. The conclusion made that PGPB coated fertilizer application was effective in improving the morphological and biochemical parameters of wheat in water stress condition.…”
Section: Resultsmentioning
confidence: 99%
“…In areas where cropping systems are intensive, supplementing soil nutrients by use of chemical fertilizers has attained inevitable importance for obtaining optimum yield of crops [6]. However, their utilization efficiency remains low, due to losses through volatilization, denitrification, leaching and ultimately fixed with clay particle and become unavailable to crop plants [7]. Among various techniques, exogenous application of silicon [6], potassium (K + ), salicylic acid (SA), glycinebetaine (GB) and proline as major organic osmolytes [7,8] are believed to play a vital role against various a biotic and biotic stresses such as drought, salinity, extreme temperatures, UV radiation and heavy metals and pest attack.…”
Section: Introductionmentioning
confidence: 99%